Isolation and Identification of Lignans and Other Phenolic Constituents from the Stem Bark of Albizia julibrissin Durazz and Evaluation of Their Nitric Oxide Inhibitory Activity - Wei Li; Hye Jin Yang (Molecules, 2020)
A dibenzylbutane-type lignan (16), along with eight furofuran-type (1–8), five furan-type (9–13), two dibenzylbutane-type (14 and 15), two bibenztetrahydronaphthalene-type lignans (17 and 18), two neolignans (19 and 20), and six phenolic derivatives (21–26) were isolated from an MeOH extract of the stem bark of Albizia julibrissin Durazz. The chemical structures of the obtained compounds were elucidated by nuclear magnetic resonance (NMR) and mass spectrometry (MS) analyses. Of the evaluated compounds, 14 were isolated from A. julibrissin and the Fabaceae family for the first time. Anti-inflammatory effects of the isolated analogs were investigated in terms of the inhibition of the nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated murine RAW264.7 macrophage cells. Ten compounds (10–12, 14, and 17–22) displayed significant dose-dependent inhibitory effects against the NO production, with IC50 values ranging from 5.4 to 19.2 µM. Moreover, eight compounds (1–4, 9, 13, 15, and 16) exhibited moderate inhibitory activities, with IC50 values ranging from 21.0 to 62.5 µM.